Analisis User Exprience Pada Web Dapodik Dinas Pendidikan Oku Selatan Menggunakan Metode System Usability Scale (SUS) - Apriliansyah, Rendi; Halim, R. M. Nasrul (LPPM STIKOM Tunas Bangsa, 2024)
The Dapodik application is a web-based data collection application which is one of the main sources for formulating government policies. In the Dapodik application, there is several data that is managed, including school data, infrastructure, students, teachers and education staff. The data or information produced is influenced by the quality of the Dapodik application itself. This research aims to analyze the user experience of the South OKU Regency Dapodik website using the System Usability Scale (SUS) method. This method is used for user interface and user experience (UX) from the perspective of usability and user satisfaction. The evaluation results are then analyzed to identify problems found in the user experience. The final SUS score from the responses of 30 respondents was 53.4, indicating that overall this application is in the OK category with an adequate level of usability. Ease of use, data input processing speed, and interface display received high ratings from respondents, reflecting that the application is well designed in terms of functionality and user friendliness